Strengthening the environment dimensions of the sustainable development goals in asia and the pacific knowledge sharing workshop proceedings.
This publication summarizes discussions and information shared during a Knowledge Sharing Workshop on Strengthening the Environment Dimensions of the Sustainable Development Goals in Asia and the Pacific. The workshop is an output of a technical assistance project, Supporting the Implementation of Environment-Related in Asia and the Pacific, to help policy makers integrate SDGs 12, 14, and 15 and select targets that are environment-related into development plans, policies, and programs.